A lipid droplet-specific fluorescence probe for atherosclerotic plaque imaging. Issue 13 (9th June 2022) - Chen, Jingruo; Li, Shufen; Ma, Di; Li, Lilan; Zhuang, Weihua; Chen, Mao
Abstract : The dysregulation of lipid droplets (LDs) is closely related to atherosclerosis (AS), while the role of LDs during the pathological processes remains mysterious. Herein, a LDs specific probe TBI was developed to help to study the role of LDs in AS. Abstract : The dysregulation of lipid droplets (LDs) is closely related to certain metabolic diseases, while the role of LDs during pathological processes remains mysterious. It would be of great value to monitor the dynamic changes of LDs in a visible way so as to study their biological functions. In this study, we report a LD-specific fluorescence probe TBI for precise LD-targeting imaging in cells and atherosclerotic tissues. TBI exhibited great biocompatibility, remarkable oil-enhanced fluorescence emission, good photostability and impressive intracellular and tissular LD-specific imaging performance. Importantly, TBI could efficiently stain the LDs at a low concentration of 50 nM, and the motion tracking of LDs could be observed via fluorescence imaging. Moreover, TBI could efficiently light up the LD distribution in mouse atherosclerotic plaques with high resolution, which revealed the ultra-structure of atherosclerotic plaques. In conclusion, these results imply that TBI could be a potential tool for investigating the physiological and pathological role of LDs.